TEKNIK BERPIKIR TINGKAT TINGGI MELALUI LOGIKA INDUKTIF DAN DEDUKTIF PERSPEKTIF ARISTOTELES - Nuriyatul Khanifah; Izza Faridatul Kamilah; Moh. Faizin (Jurnal Genta Mulia, 2024)
The ability to think critically and logically in making appropriate and effective decisions is important, especially in logical thinking. The purpose of this article is to discuss Aristotle and logic, inductive and deductive logic in higher order thinking, the combination of inductive and deductive logic in higher order thinking and its benefits and implications. The method used in this article is library research. The reasoning system known as deductive logic looks at the rules of valid conclusions based on formulations and conclusions that are generated as a condition derived from the premise. Inductive reasoning relies on making inferences based on direct knowledge and experience. The results achieved through inductive reasoning are not necessarily accurate with absolute certainty, but rather have a certain degree of probability or possibility. Observing some specific situations or examples and then making generalizations based on patterns or regularities found is an example of inductive reasoning. In contrast, deductive reasoning draws certain conclusions from certain premises by applying general laws or logical norms. As long as the premises and reasoning are correct, the conclusions obtained through deductive reasoning are always correct. Thus, inductive and deductive logic help us to have correct and precise knowledge in thinking and avoid misunderstandings.